Characterization of Pyrolytic Tars Derived from Different Biomasses - Saires, Paula Judith (2024)
The pyrolysis of three different biomasses, rice husk (RH), zoita wood sawdust (ZW) and pine wood sawdust (PW), was studied at 500 ºC in a multipurpose unit at the bench scale to determine the yields of the different products and the compositions and properties of the liquid products, particular emphasis being given to the alquitranous fractions (tars). It was possible to link the characteristics of the tars with the compositions of the raw biomasses and verify their potential in various applications. Analytical techniques employed in the characterization of biomasses included ultimate and proximate analysis, lignocellulosic material and thermogravimetry-mass spectrometry analysis (TG-MS). Elemental analysis, gas chromatography-mass spectrometry (GC-MS), nuclear magnetic resonance spectroscopy (1H NMR), Fourier transform infrared spectroscopy (FTIR) and size exclusion chromatography (SEC) were used to characterize tars. Tar yields were 1.8, 7.4 and 4.0 %wt. in the cases of RH, ZW y PW, respectively. Tars showed higher carbon contents, between 60.3 and 62.2 %wt., and lower oxygen content, between 28.8 and 31.6 %wt., than the corresponding raw biomasses. The main components of tars had aromatic base, phenols representing more than 50 %. Tar RH included more guaiacols, while Tar ZW and PW included more phenols and alkylated phenols.